P5 The use of cardiopulmonary exercise testing in idiopathic pulmonary fibrosis: feasibility and correlation with quality of life measures. (12th November 2019) - Davis, RJ; Barratt, SL; Viner, J; Dixon, C; Morley, A; Adamali, H; Maskell, N
Abstract : Introduction: The heterogeneity of idiopathic pulmonary fibrosis (IPF) in terms of disease course and treatment response leads to challenges for patients and clinicians in terms of optimal timing for transplantation and/or end of life discussions. The use of cardiopulmonary exercise testing (CPET) in IPF prognostication remains largely unexplored. Objectives: To explore the feasibility of undertaking CPET in this population; To explore the correlation between baseline CPET variables, physiological variables and quality of life (QOL) scores. Methods: Consecutive IPF patients (n=74) were approached, with prospective recruitment of 42 participants. Patients with FVC <50% and/or DLCO <50% were excluded. King's Brief ILD (K-BILD) questionnaire assessed QOL. Patients undertook incremental exercise testing to maximal exertion using a cycle ergometer, with contemporaneous physiological testing (FVC, DLCO). Results: 32 patients were excluded from the study (22 screening failures, 10 declined), with study attrition of an additional 10 patients (n=4 withdrew consent, n=1 death prior to testing, n=5 developed exclusions). Thirty-two patients (23 mild IPF with FVC>80%, 9 moderate IPF with FVC 50–80%), 26M:6F and median age (IQR) 75 years (71–79), underwent CPET. One patient failed to reach anaerobic threshold (AT) and was excluded from the analysis. Median (IQR) pulmonary and exercise results were: FVC 92% (75–102), DLCO 62% (54–69), minimum SpO2 93% (88–95), VO2 peak/kg 21 (17.4–23.8) mL.kg -1 .min -1 and VE /VCO2 27.2 (25.4–30.5). Median (IQR) QOL scores for each domain were: total K-BILD 64.4 (58.1–68.7), psychological 68.3 (56.9–80.9), breathlessness/activity (B/A) 50.2 (48–62.7) and chest symptoms 85.2 (73.4–85.2) (Table1). VO2 peak/kg correlated with chest (r=0.36, p=0.049) and B/A (r=0.43, p=0.016) domains of the K-BILD questionnaire. VO2 peak/kg at AT also correlated with total K-BILD scores r=0.37, p=0.039 and chest domains (r=0.535, p=0.002). Total KBILD scores did not correlate with%FVC (r=0.26, p=0.15), %DLCO predicted (r=0.11, p=0.544) or SpO2 (r=0.01, p=0.959) (Spearman's). Conclusions: Initial results suggest CPET is a feasible method of testing in mild-moderate IPF. Whilst QOL did not correlate with baseline FVC and DLCO, the relationship between oxygen consumption and QOL measures, requires further exploration. Longitudinal data will hopefully provide further information on the usefulness of CPET as a prognostic marker.